2020
DOI: 10.1101/2020.08.11.245035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and molecular basis for Cardiovirus 2A protein as a viral gene expression switch

Abstract: Encephalomyocarditis virus 2A protein is a multi functional virulence factor essential for efficient virus replication with roles in stimulating programmed -1 ribosomal frameshifting (PRF), inhibiting cap-dependent translational initiation, interfering with nuclear import and export and preventing apoptosis of infected cells. The mechanistic basis for many of these activities is unclear and a lack of structural data has hampered our understanding. Here we present the X-ray crystal structure of 2A, revealing a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 112 publications
2
24
0
Order By: Relevance
“…We define a minimal TMEV stimulatory element necessary for 2A binding and show that the protein forms a 1:1 RNA-protein complex with nanomolar affinity. We provide evidence that the alternative pseudoknot-like conformation recently described for the EMCV stimulatory element ( 28 ) is also likely to be present in TMEV and other cardioviruses. Finally, we use metabolic labelling and ribosome profiling to study 2A-stimulated frameshifting and translation of the TMEV genome at sub-codon resolution in infected cells.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…We define a minimal TMEV stimulatory element necessary for 2A binding and show that the protein forms a 1:1 RNA-protein complex with nanomolar affinity. We provide evidence that the alternative pseudoknot-like conformation recently described for the EMCV stimulatory element ( 28 ) is also likely to be present in TMEV and other cardioviruses. Finally, we use metabolic labelling and ribosome profiling to study 2A-stimulated frameshifting and translation of the TMEV genome at sub-codon resolution in infected cells.…”
Section: Introductionsupporting
confidence: 55%
“…Our previous investigations of protein-stimulated frameshifting in EMCV and TMEV have revealed that the viral 2A protein acts in complex with a stem-loop downstream of the slippery sequence, and that this interaction can be disabled by mutating either a conserved cytosine triplet in the loop or a pair of conserved arginine residues in the protein ( 11 , 22 , 23 ). More recently, we solved the structure of EMCV 2A, revealing a novel protein fold that permits binding to both the stem-loop and to ribosomal RNA with high affinity ( 28 ). However, 2A protein sequences are highly divergent within cardioviruses, and the TMEV protein shares only ∼27% pairwise amino acid sequence identity with its EMCV orthologue.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by our ensemble and single-molecule analysis, ZAP-S directly interacts with the SARS-CoV-2 frameshift signal and alters folding of the RNA element. However, several trans-acting factors including the cardiovirus 2A and SFL were also shown to bind to ribosomes 15,53 . To explore the possibility of whether ZAP also interacts with ribosomes during translation, we performed ribosome pelleting assay (Fig.…”
Section: Zap-s Interacts With Translating Ribosomesmentioning
confidence: 99%
“…These derivations were statistically analyzed to identify the folding events and their coordinates. For data fitting, we employed a combination of two worm-like chain models (WLC1 for the fully folded double-stranded parts and WLC2 for the unfolded single-stranded parts) as described previously 53 . Firstly, the initial contour length of the folded RNA was set to 1231 nm, and the persistence length of the double-stranded part was fitted 53 .…”
Section: Optical Tweezers Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation